Strategies for new and improved vaccines against ticks and tick‐borne diseases. (13th June 2016) - de la Fuente, J.; Kopáček, P.; Lew‐Tabor, A.; Maritz‐Olivier, C.
Summary: Ticks infest a variety of animal species and transmit pathogens causing disease in both humans and animals worldwide. Tick–host–pathogen interactions have evolved through dynamic processes that accommodated the genetic traits of the hosts, pathogens transmitted and the vector tick species that mediate their development and survival. New approaches for tick control are dependent on defining molecular interactions between hosts, ticks and pathogens to allow for discovery of key molecules that could be tested in vaccines or new generation therapeutics for intervention of tick–pathogen cycles. Currently, tick vaccines constitute an effective and environmentally sound approach for the control of ticks and the transmission of the associated tick‐borne diseases. New candidate protective antigens will most likely be identified by focusing on proteins with relevant biological function in the feeding, reproduction, development, immune response, subversion of host immunity of the tick vector and/or molecules vital for pathogen infection and transmission. This review addresses different approaches and strategies used for the discovery of protective antigens, including focusing on relevant tick biological functions and proteins, reverse genetics, vaccinomics and tick protein evolution and interactomics. New and improved tick vaccines will most likely contain multiple antigens to control tick infestations and pathogen infection and transmission.